Proposal of a Blended Educational Technological System: An approach from system science - Olmos-Peña, Samuel; Nares-Hernández, José Julio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The adequate training of professionals presents a worldwide educational challenge, this challenge is of a multifactorial nature and has been addressed from different scientific and academic fields. The health pandemic forced the temporary closure of universities. This closure clearly shows multiple deficiencies in the implementation of hybrid technological systems. In this context, a comprehensive proposal was developed to address the solution needs of a hybrid education. To formulate the model was conducted a literature review to identify the critical success factors in hybrid education with use technological resources, the operation of a higher education institution was characterized. Once that it was determined, several digital educational platforms were identified. From this, the model of viable systems was used, and was obtained a first approximation of the model to later test its implementation.